2016
DOI: 10.1021/acsmacrolett.6b00183
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Surface Transport Is a Combination of in-Plane Diffusion and Desorption-Mediated Flights

Abstract: Previous studies of polymer motion at solid/liquid interfaces described the transport in the context of a continuous time random walk (CTRW) process, in which diffusion switches between desorption-mediated “flights” (i.e., hopping) and surface-adsorbed waiting-time intervals. However, it has been unclear whether the waiting times represented periods of complete immobility or times during which molecules engaged in a different (e.g., slower or confined) mode of interfacial transport. Here we designed high-throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…the distributions were broader) on surfaces corresponding to a stronger adsorbate-surface interaction. Previous work has suggested that surface diffusion was influenced by multiple effects, e.g., adsorbate-surface interactions (desorption rate), re-adsorption probability, physical obstacles, chemical surface heterogeneity, etc [24,[39][40][41][42][43]. The results presented here provide a comprehensive picture of how and why adsorbate-surface interactions influence interfacial motion.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…the distributions were broader) on surfaces corresponding to a stronger adsorbate-surface interaction. Previous work has suggested that surface diffusion was influenced by multiple effects, e.g., adsorbate-surface interactions (desorption rate), re-adsorption probability, physical obstacles, chemical surface heterogeneity, etc [24,[39][40][41][42][43]. The results presented here provide a comprehensive picture of how and why adsorbate-surface interactions influence interfacial motion.…”
mentioning
confidence: 66%
“…While interfacial diffusion is nominally two-dimensional (2D) and conventionally described in terms of 2D Brownian motion, longstanding theoretical models [7][8][9][10][11][12][13][14][15][16] have predicted that interfacial mass transport could actually be dominated by "flights" through an adjacent liquid phase, which would dramatically alter the nature of interfacial molecular motion; an understanding of this process is necessary in order to rationally control mass transport at surfaces. Recent experimental results indirectly support these predictions, by measuring the 2D projection of trajectories for atoms, molecules, polymers, and nanoparticles, in thin films, at solid/liquid interface, and on lipid bilayers, which can be represented as an intermittent process, with periods of apparent immobility alternating with long "flights" comprising a heavy-tailed distribution [17][18][19][20][21][22][23][24][25][26]. However, the evidence for the presence of three-dimensional (3D) hops remains indirect, and critical aspects of the proposed "hopping" process remain a mystery.…”
mentioning
confidence: 94%
“…[24,[39][40][41][42][43]. The results presented here provide a comprehensive picture of how and why adsorbate-surface interactions influence interfacial motion.…”
Section: Prl 119 268001 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 78%
“…While interfacial diffusion is nominally two dimensional (2D) and conventionally described in terms of 2D Brownian motion, longstanding theoretical models [7][8][9][10][11][12][13][14][15][16] have predicted that interfacial mass transport could actually be dominated by "flights" through an adjacent liquid phase, which would dramatically alter the nature of interfacial molecular motion; an understanding of this process is necessary in order to rationally control mass transport at surfaces. Recent experimental results indirectly support these predictions by measuring the 2D projection of trajectories for atoms, molecules, polymers, and nanoparticles, in thin films, at solid-liquid interface, and on lipid bilayers, which can be represented as an intermittent process with periods of apparent immobility alternating with long flights comprising a heavy-tailed distribution [17][18][19][20][21][22][23][24][25][26]. However, the evidence for the presence of three-dimensional (3D) hops remains indirect, and critical aspects of the proposed "hopping" process remain a mystery.…”
mentioning
confidence: 92%
“…Surface diffusion of small molecules (10)(11)(12) and polymers (13)(14)(15)(16), unlike that of proteins, has been widely reported in liquid-solid systems. In reverse-phase liquid chromatography, hydrocarbons have been reported to diffuse at the interfacial region near the end of the alkyl chains of the stationary phase (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%